Analysis of The Effect of Maintenance and Calibration Against Localizer Equipment Performance - Feti Fatonah; Lilis Kurnianingsih; Taruna Jaya (CV. Syntax Corporation Indonesia, 2023)
To support aviation safety, equipment facilities are needed that are able to provide information, guidance, and signs so that aircraft are safe from the time they take off until they land. So that the risk of landing failure can be minimized, equipment is needed that can guide aircraft to land correctly and safely (Supriyadi, 2012). One of the navigation aids is the Instrument Landing System (ILS). An instrument Landing System (ILS) is an instrument landing tool (non-visual) that assists pilots in carrying out aircraft approach and landing procedures at an airport. ILS provides information that is accurate enough so that pilots can make landings in all weather conditions. This really helps airports in carrying out their services, so that air traffic activities can run safely and smoothly. There are three information components of the ILS system, namely: Localizer Transmitter as a guide to the right/left of the runway axis/axle, Glide Slope Transmitter as a guide to the landing angle on the runway axis. Marker Beacon (Inner, Middle, Outer Marker Beacon) which is located at a certain distance from the threshold as a horizontal distance guide to the runway threshold. In aviation navigation services, Localizer equipment must be ready to operate and maintained, so maintenance and reporting procedures are required which have been stipulated in the Guidelines for Maintenance and Reporting of Aviation Electronics and Electrical Facilities Equipment. Apart from maintenance, navigation aids require calibration to ensure that the performance of the Localizer navigation aids is in good condition and can provide a good angle for landing in accordance with the provisions of the Instructions and Procedures for Carrying Out Calibration of Flight Facilities and Procedures. The method used in this research is a quantitative method. Based on the results of the F test, all independent variables, namely maintenance, and calibration, simultaneously or together influence the performance of the localizer equipment. This is proven by the calculated F result of 24.403 > F table 3.18 and a significance value of 0.000 < 0.05.